2006
DOI: 10.1111/j.1445-2197.2006.03666.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Early Aggressive Management of Empyema Thoracis

Abstract: Video-assisted thoracoscopic evacuation and chest tube insertion in situ is a new therapeutic approach for pleural empyema that shortens hospital stay and reduces the necessity of open decortication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(77 citation statements)
references
References 9 publications
1
73
0
3
Order By: Relevance
“…To date, two randomised trials have compared primary VATS against conservative chest tube drainage in adult patients and neither showed any major clinical benefits, except for a slightly shorter hospital stay (mean¡SD; 8.7¡0.9 versus 12.8¡1.1 days) [105,106]. Two randomised trials in paediatric patients also failed to show significant advantages of surgery [102,107], although both of these studies suggested lower treatment costs in the fibrinolysis groups, although these were secondary analyses.…”
Section: Surgery For Empyemamentioning
confidence: 99%
“…To date, two randomised trials have compared primary VATS against conservative chest tube drainage in adult patients and neither showed any major clinical benefits, except for a slightly shorter hospital stay (mean¡SD; 8.7¡0.9 versus 12.8¡1.1 days) [105,106]. Two randomised trials in paediatric patients also failed to show significant advantages of surgery [102,107], although both of these studies suggested lower treatment costs in the fibrinolysis groups, although these were secondary analyses.…”
Section: Surgery For Empyemamentioning
confidence: 99%
“…Although surgery has been advocated as initial treatment for all patients with pleural infection [19][20][21] , evidence to support the unselected use of surgery in all patients is lacking. Two moderate sized paediatric clinical trials showed no clinical benefit and greater cost from this approach 12,22 and two small adult randomised trials did not use robust outcome methodologies 23,24 . Surgical thoracic procedures are associated with anaesthetic and perioperative risks 25 , and thoracotomy causes substantial post-operative pain 26 up to 3 years after operation 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the fibrinolytic agent can be applied for improvement of drainage. A series studies also considered that the streptokinase or urokinase used in the pleural cavity can reduce hospital stay, prognosis improvement (9,(47)(48)(49)(50)(51) and prevent catastrophic hazards (4,50,52,53). However, the largest random and controlled clinical study considers that streptokinase application in the pleural cavity has failed to improve hospital stay, death rate and others, to date (22) and a researcher also considers that the fibrinolytic agent has failed to reduce fatality rate (54).…”
Section: Intrapleural Cavity Injectionmentioning
confidence: 99%